Kesetaraan Gender Dalam Melakukan Kegiatan Ekonomi Keluarga - Elsyan Rienette Marlissa; Agustina Ester Antoh (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
This service aims to provide education and knowledge about gender-responsive family economic activities to the Kingmi Eklesia Angkasa Church Congregation - Jayapura City. The method used is lecture, discussion and face-to-face question and answer. The impact of this service is to provide knowledge and understanding of the socialization of the quality of activities in carrying out gender-responsive family economic activities for each family in the Kingmi Eklesia Angkasa Church Congregation.